External pressures distribution on tensioned membrane roofs (2019)
The tensioned membrane roofs have wide areas of applications. One of them is agricultural structure. It can be used for intensive and extensive animal production structures or plant production. One of the most important parameters in these objects with animal production is thermal comfort. It is necessary to ensure the efficient ventilation, in the best case the natural. Optimal shape of building and roof has strong impact on ventilation parameter. The first stage of the article is a preliminary investigation of the optimal shape of the duopitch roof from the point of view of wind loading. Duopitch roofs were investigated experimentally in a wind tunnel at the scaled rigid models. Experiments are carried out in the Boundary Layer Wind Tunnel in Bratislava. Wind conditions as the intensity of turbulence, wind speed and direction of wind are crucial for overall wind loads and effectiveness of natural ventilation. The aim of our article is a wind analysis of various shapes of duopitch boundary tensioned membranes with various pitch angles and wind directions. The purpose of this work is to quantify the external pressure coefficient. The results of wind tunnel measurements are analyzed in pressure coefficient maps. They can be used for more efficient design of agricultural structures.